2016
DOI: 10.1111/cmi.12614
|View full text |Cite
|
Sign up to set email alerts
|

Host glycosylation pathways and the unfolded protein response contribute to the infection byFrancisella

Abstract: Protein glycosylation processes play a crucial role in most physiological functions, including cell signalling, cellular differentiation and adhesion. We previously demonstrated that rapid deglycosylation of membrane proteins was specifically triggered after infection of human macrophages by the bacterial pathogen Francisella tularensis. Using a glycan processing gene microarray, we found here that Francisella infection modulated expression of numerous glycosidase and glycosyltransferase genes. Furthermore, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Francisella infection modifies the unfolded protein response (UPR) (Barel et al, 2016) and manipulates autophagy (Miller and Celli, 2016). Both processes are involved in maintaining cellular homeostasis and helping destroy invading microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Francisella infection modifies the unfolded protein response (UPR) (Barel et al, 2016) and manipulates autophagy (Miller and Celli, 2016). Both processes are involved in maintaining cellular homeostasis and helping destroy invading microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, using a glycan processing gene microarray (Chacko et al, 2011), we observed significant changes in the level of glycosyltransferase and glycosidase gene expression profiles in human THP-1 monocytes, infected for 24 h with F. tularensis LVS (Barel et al, 2016). Expression of eight genes, encoding four glycosyltransferases and four glycosidases, was down-regulated upon infection.…”
Section: Host Point Of Viewmentioning
confidence: 99%
“…F. tularensis strain LVS has been shown to trigger rapid deglycosylation of host membrane proteins (Barel et al, 2012) due to the expression of enzymes producing N - and O -linked glycosylation (Barel et al, 2016). An important effect related to intracellular existence of Francisella is an increased expression of GRP78/BiP (Barel et al, 2016), which is an ER stress chaperone required for proper folding and assembly of newly synthetized proteins (Lee, 2005; Luo et al, 2006). In general, the expression of glycosylated GRP78/BiP is followed by activation of IRE1 (Barel et al, 2016) through a binding/release mechanism.…”
Section: Innate Immune Recognition Of Intracellular Bacteria: Francismentioning
confidence: 99%
“…An important effect related to intracellular existence of Francisella is an increased expression of GRP78/BiP (Barel et al, 2016), which is an ER stress chaperone required for proper folding and assembly of newly synthetized proteins (Lee, 2005; Luo et al, 2006). In general, the expression of glycosylated GRP78/BiP is followed by activation of IRE1 (Barel et al, 2016) through a binding/release mechanism. IRE1 is an ER-transmembrane protein important for sensing and responding to misfolded protein-GRP78/BiP dissociation and is one of three recently known arms of UPR (Hetz and Papa, 2018).…”
Section: Innate Immune Recognition Of Intracellular Bacteria: Francismentioning
confidence: 99%
See 1 more Smart Citation